Depression is differentially related to cognitive and biomarker outcomes among Mexican Americans - O’Bryant, Sid E.; Petersen, Melissa; Hall, James; Johnson, Leigh A. (Frontiers in Psychiatry, 2022)
Introduction: Despite tremendous advancements in the research of Alzheimer’s disease (AD), Mexican Americans, who reflect 65% of the U.S. Hispanic community, remain severely underrepresented in research. Our data demonstrates that risk factors for, and biomarkers of, AD are different among Mexican Americans as compared to non-Hispanic whites. Here we examined the impact of depressive symptoms on cognitive and AD-relevant biomarker outcomes among Mexican Americans. Methods: Data was examined from 1,633 (852 Mexican American, 781 non-Hispanic whites) of the Health & Aging Brain Study – Health Disparities (HABS-HD). Depression was assessed using the Geriatric Depression Scale while cognition was measured using detailed neuropsychological testing. Plasma biomarkers of Aβ40, Aβ42, total tau and NfL were examined in addition to MRI-based neurodegeneration. PET amyloid data was available in a subset of participants. Results: Depressive symptoms were significantly associated with cognitive testing results among both Mexican Americans and non-Hispanic whites. However, depression was only significantly associated with cognitive outcomes and plasma biomarkers among Mexican American APOEε4 non-carriers. Discussion: Depressive symptoms are more commonly endorsed by Mexican Americans and these symptoms are more strongly associated with cognitive and AD-biomarker outcomes among this ethnic group. However, depression scores were only related to AD-outcomes among APOEε4 non-carriers within the Mexican American group. These findings can aid in the development of a population-informed precision medicine for treating and preventing cognitive loss among Mexican Americans.